La política pública para la formación investigativa del profesorado en Colombia - Cano Quintero, María Constanza (Universidad Santiago de Cali, 2020)
Public policies as a matter of inquiry, involve a variety of views in research, reflections and studies. It can be understood that it causes diversity of reactions, interpretations and questions; given that it is a subject that is complex, due to its direct and indirect interference in almost all social spheres. Education as a central component of society, is no stranger to the impact that public policies have on their development. This document includes the documentary review, prepared to identify the characteristics of public policy in Colombia, in which the Research Training (FI) of teachers in this country is leveraged, especially in the context of the initial education of teachers. The review was carried out in the public policies issued by the Ministry of National Education, between law 115 of 1994 to decree 2450 of 2015, contained in decree 1075 of 2015. The documentary review was implemented as a technique to obtain the information and the registration matrix as a format used to establish, organize and select what exists in the documents, of interest to the review. Among the findings and conclusions, the existence of a Public Policy for Teacher Training in Research in its Initial Education process is recognized and valued, given that research skills and competencies are considered as an added value to the knowledge that all teacher must have.